(untitled) (Bangladesh Critical Care Journal, 2026)
Pituitary apoplexy, while classically acute, can present insidiously as chronic apoplexy, posing significant diagnostic challenges. We report a 60-year-old male with multiple comorbidities who presented with progressive weakness and neck pain following a gastrointestinal illness. He was found to have severe symptomatic hyponatremia (Na+ 115 mmol/L) with a biochemical profile suggestive of the Syndrome of Inappropriate Anti-Diuretic Hormone (SIADH). Brain MRI demonstrated sellar–suprasellar pituitary mass with heterogeneous signal intensity and hemorrhagic components, showing peripheral rim enhancement on gadolinium-enhanced. Further evaluation revealed a profoundly low serum cortisol (< 1.8 μg/dL) and low prolactin. This case underscores that a patient with adrenal insufficiency secondary to chronic pituitary apoplexy may present as hyponatremia with SIADH-like features. Bangladesh Crit Care J March 2026; 14 (1): 52-54